Violência de Gênero e Direito Penal: tipificação do Feminicídio e Possíveis Respostas Penais = Gender Violence and Criminal Law : typification of Femicide and Possible Criminal Answers - Mendes Mesquita, Luisa Angélica (Revista Eletrônica de Direito Penal e Política Criminal, 2018)
This article aims to provide if the typification of femicide/feminicide is the legitimate way to prevent and eradicate gender violence. As it is known violence against women is historical and structural, it is related to women’s subordinated position in the patriarchal sociocultural order. There is a standard of control and oppression that leads to discrimination, exploration and creation of stereotypes which are passed on between generations and reproduced in a reiterated and multifaceted way in public and private places. In order to react to this situation, many international conventions were created and therefrom, a series of legal reforms were done by Latin-American countries. Thus, the typification of femicide/feminicide occurred in many countries and this must be questioned by the Crime and Punishment Symbolism. Therefore, from a comparative study and from a critical perspective based on a Minimal Criminal Law it is intended to disclose if this is the legitimate way to prevent and eradicate gender violence.